Correlation between overt hyperthyroid and subclinical hyperthyroid and cognitive impairment in Dr. Sardjito General Hospital, Yogyakarta, Indonesia - Berkat Hia Pernodjo Dahlan Abdul Ghofir (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Hyperthyroidism is a metabolic imbalance resulting from excessive production of thyroid hormones.Overt or subclinical hyperthyroid prevalence has reached 20%. The differences in thyroid statusinduce apoptosis in adult cerebral cortex. Triiodothyroxine (T3) acts directly on the cerebralcortex mitochondria and induces the release of cytochrome-c which leads to apoptosis. Theincrease of hormone levels encountered in hyperthyroidism which is associated with an increasein necrotic death of neurons and oxidative stress has a negative effect on cognition. Severalstudies demonstrated the significant association of hyperthyroidism with cognitive impairment,despite remaining as controversial results. The study aimed to evaluate the correlation betweenovert hyperthyroid and subclinical hyperthyroid and cognitive impairment in hyperthyroidismpatients. This was a cross-sectional study involving 68 patients of hyperthyroidism who weretreated in Endocrine Clinic of Dr. Sardjito General Hospital, Yogyakarta. The inclusion criteriawere hyperthyroidism based on anamnesis, clinical examination and laboratory tests, age of 20-60 years, symptoms of hyperthyroidism, and minimum education of elementary school. Therelationship of hyperthyroidism and cognitive impairment, and multivariate analysis was analyzedby Chi-square and logistic regression tests, respectively. The results were considered as statisticallysignificant if the value of p was <0.05. The results showed that overt hyperthyroidism hadsignificantly associated with cognitive impairment (p = 0.021). Another variable associatedwith cognitive impairment was female gender (p = 0.019). In a multivariate analysis, the variablesof overt hyperthyroidism (p = 0.024) and sex (p = 0.025) had independent association withcognitive impairment. In conclusion, this study found that overt hyperthyroidism had a significantassociation with incidence of cognitive impairment compared to subclinical hyperthyroidism.Keywords: hyperthyroidism - overt - subclinical - cognitive - mini-mental state examination